The Relationship of Children's Sleep Patterns with Learning Concentration Levels in Children aged 7-12 Years - Tunik (CV. Get Press Indonesia, 2026)
Low learning concentration in children is often linked to irregular sleep habits, such as going to bed late or experiencing sleep disturbances, which can reduce sleep quality and affect classroom performance. This study aimed to examine the relationship between sleep patterns and learning concentration among students. A quantitative correlational approach was used with a sample of 75 students from Grades 2–6 at SD Negeri 37 Anduring Padang, selected randomly. Data were collected through sleep pattern questionnaires and classroom observation of learning concentration, then analyzed using Pearson correlation. The results showed that most children had irregular sleep patterns, with 40% sleeping less than eight hours per night, while_toggle The majority of students displayed moderate learning concentration levels. Statistical analysis revealed a fairly strong positive relationship between regular sleep patterns and learning concentration (r = 0.65, p < 0.05). These findings suggest that adequate and consistent sleep plays an important role in improving children’s learning concentration. Therefore, parents and schools should work together to promote healthy sleep habits to support optimal learning outcomes in children aged 7–12 years.